Management of obesity across women's life course: FIGO Best Practice Advice. (12th January 2023) - Maxwell, Cynthia V.; Shirley, Rachelle; O'Higgins, Amy C.; Rosser, Mary L.; O'Brien, Patrick; Hod, Moshe; O'Reilly, Sharleen L.; Medina, Virna P.; Smith, Graeme N.; Hanson, Mark A.; Adam, Sumaiya; Ma, Ronald C.; et al.
Abstract: Obesity is a chronic, progressive, relapsing, and treatable multifactorial, neurobehavioral disease. According to the World Health Organization, obesity affects 15% of women and has long‐term effects on women's health. The focus of care in patients with obesity should be on optimizing health outcomes rather than on weight loss. Appropriate and common language, considering cultural sensitivity and trauma‐informed care, is needed to discuss obesity. Pregnancy is a time of significant physiological change. Pre‐, ante‐, and postpartum clinical encounters provide opportunities for health optimization for parents with obesity in terms of, but not limited to, fertility and breastfeeding. Pre‐existing conditions may also be identified and managed. Beyond pregnancy, women with obesity are at an increased risk for gastrointestinal and liver diseases, impaired kidney function, obstructive sleep apnea, and venous thromboembolism. Gynecological and reproductive health of women living with obesity cannot be dismissed, with accommodations needed for preventive health screenings and consideration of increased risk for gynecologic malignancies. Mental wellness, specifically depression, should be screened and managed appropriately. Obesity is a complex condition and is increasing in prevalence with failure of public health interventions to achieve significant decrease. Future research efforts should focus on interprofessional care and discovering effective interventions for health optimization. Synopsis: Obesity is a complex and multifactorial medical condition that requires important considerations over a woman's life course and during pregnancy.